ANALYSIS OF CHALLLENGES FACED BY GST OFFICIALS AT THE TIME OF GST IMPLEMENTATION – A STUDY IN THE STATE OF HARYANA (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The implementation of Goods and Services Tax (GST) aimed to address deficiencies in the preceding tax system and establish a unified market in India.The decision was not akin to instantaneous click button that could be immediately switched on; rather, it entailed a comprehensive transition period to facilitate the adoption of the proposed change and the challenges are always inevitable with changes.This research endeavors to identify and analyze the challenges encountered by GST officials during the implementation of GST. The study relies exclusively on primary data, with officers from the Central Goods and Services Tax (CGST) and State Goods and Services Tax (SGST) being chosen as respondents. A structured questionnaire was utilized to collect data from 360 respondents. The findings of the study reveal a noteworthy correlation between the officers' category and the challenges faced by them during the GST implementation phase. The study suggests that the delayed establishment of tribunals, increased work pressure, and inadequate/inefficient training programs were the most notable challenges confronted by the officials. Additionally, the research offers recommendations to address and overcome these challenges.